Expression of thyrotropin-releasing hormone receptors in rat testis and their role in isolated Leydig cells - Yong Zhao; Wu-Gang Hou; Hua-Ping Zhu; Jie Zhao; Rui-An Wang; Ruo-Jun Xu; Yuan-Qiang Zhang (Cell and Tissue Research, 2008)

Environmental controls over carbon exchange of three forest ecosystems in eastern China - GUI‐RUI YU; LEI‐MING ZHANG; XIAO‐MIN SUN; YU‐LING FU; XUE‐FA WEN; QIU‐FENG WANG; SHENG‐GONG LI; CHUAN‐YOU REN; XIA SONG; YUN‐FEN LIU; SHI‐JIE HAN; JUN‐HUA YAN (Global Change Biology, 2008)
Net ecosystem productivity (NEP) was continuously measured using the eddy covariance (EC) technique from 2003 to 2005 at three forest sites of ChinaFLUX. The forests include Changbaishan temperate mixed forest (CBS), Qianyanzhou subtropical coniferous plantation (QYZ), and Dinghushan subtropical evergreen broad‐leaved forest (DHS). They span wide ranges of temperature and precipitation and are influenced by the eastern Asian monsoon climate to varying extent. In this study, we estimated ecosystem respiration (RE) and gross ecosystem productivity (GEP). Comparison of ecosystem carbon exchange among the three forests shows that RE was mainly determined by temperature, with the forest at CBS exhibiting the highest temperature sensitivity among the three ecosystems. The RE was highly dependent on GEP across the three forests, and the ratio of RE to GEP decreased along the North–South Transect of Eastern China (NSTEC) (i.e. from the CBS to the DHS), with an average of 0.77 ± 0.06. Daily GEP was mainly influenced by temperature at CBS, whereas photosynthetic photon flux density was the dominant factor affecting the daily GEP at both QYZ and DHS. Temperature mainly determined the pattern of the interannual variations of ecosystem carbon exchange at CBS. However, water availability primarily controlled the interannual variations of ecosystem carbon exchange at QYZ. At DHS, NEP attained the highest values at the beginning of the dry seasons (autumn) rather than the rainy seasons (summer), probably because insufficient radiation and frequent fog during the rainy seasons hindered canopy photosynthesis. All the three forest ecosystems acted as a carbon sink from 2003 to 2005. The annual average values of NEP at CBS, QYZ, and DHS were 259 ± 19, 354 ± 34, and 434 ± 66 g C m −2 yr −1 , respectively. The slope of NEP that decreased with increasing latitude along the NSTEC was markedly different from that observed on the forest transect in the European continent. Long‐term flux measurements over more forest ecosystems along the NSTEC will further help verify such a difference between the European forest transect and the NSTEC and provide insights into the responses of ecosystem carbon exchange to climate change in China.

Cloning and characterization of phosphorus starvation inducible Brassica napus PURPLE ACID PHOSPHATASE 12 gene family, and imprinting of a recently evolved MITE-minisatellite twin structure - Kun Lu; You-Rong Chai; Kai Zhang; Rui Wang; Li Chen; Bo Lei; Jun Lu; Xin-Fu Xu; Jia-Na Li (Theoretical and Applied Genetics, 2008)

Degradation of Hazardous Dyes in Wastewater using Nanometer Mixed Crystal TiO2 Powders under Visible Light Irradiation - Jun Wang; Ronghe Li; Zhaohong Zhang; Wei Sun; Xiaofang Wang; Rui Xu; Zhiqiang Xing; Xiangdong Zhang (Water, Air, & Soil Pollution, 2008)

Spatial distributions of organic carbon and nitrogen and their isotopic compositions in sediments of the Changjiang Estuary and its adjacent sea area - Jianhua Gao; Yaping Wang; Shaoming Pan; Rui Zhang; Jun Li; Fenglong Bai (Journal of Geographical Sciences, 2008)

Molecular cloning and characterization of two novel cellulase genes from the mollusc Ampullaria crossean - Rui Guo; Ming Ding; Si-Liang Zhang; Gen-jun Xu; Fu-kun Zhao (Journal of Comparative Physiology B, 2008)

Insulin inhibits β-adrenergic action in ischemic/reperfused heart: a novel mechanism of insulin in cardioprotection - Qiu-Jun Yu; Rui Si; Ning Zhou; Hai-Feng Zhang; Wen-Yi Guo; Hai-Chang Wang; Feng Gao (Apoptosis, 2008)